Pengaruh Prestise dan Lingkungan Sosial Terhadap Minat Mahasiswa Jurusan Perbankan Syariah UIN Raden Fatah Bekerja di Bank Syariah : Studi Kasus Mahasiswa UIN Raden Fatah Palembang - Ismi Oktavia Kartika Pradana; Hilda Hilda; M. Junestrada Diem (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of prestige and social environment on the interest of Islamic Banking Department students at UIN Raden Fatah Palembang to work in Islamic banks. Prestige and social environment are two factors that are thought to influence students' interest in working in Islamic banks. This research used a quantitative method with an incidental sampling technique using the Slovin formula to obtain 93 samples. Data was collected through questionnaires and analyzed using the PLS (Partial Least Square) analysis technique via SmartPls. The results of the research show that the Prestige variable obtained a t-statistical value of 4.349 > 1.96 with a p-value of 0.000 < less than the significance level of 0.05, so it can be explained that prestige has a positive and significant effect on student interest and the Social Environment variable obtained a t-value statistics 2,931 > 1.96 with a p-value of 0.004 < less than the significance level of 0.05, so it can be explained that the Social Environment has a positive and significant effect on students' interest in working in sharia banks. The conclusion of this research is that prestige and the social environment influence the interest of students from the Sharia Banking Department at UIN Raden Fatah Palembang to work in a sharia bank. The higher the prestige of a job and the more supportive the social environment, the higher the student's interest in working in a sharia bank.